Pathologic Changes of the Lateral Pterygoid Muscle in Patients with Derangement of the Temporomandibular Joint Disk: Objective Measures at MR Imaging - Finden, S.G.; Enochs, W.S.; Rao, V.M. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The superior head of the lateral pterygoid muscle (SHLP), which inserts on the anterior disk of the temporomandibular joint (TMJ), can spasm, contracting and exerting forward traction on the disk. This mechanism can lead to anterior displacement. In TMJ dysfunction, it is hypothesized that the SHLP will demonstrate morphologic changes with measurable changes in signal intensity related to atrophy or muscular edema, or both. The goal of this study was to evaluate the lateral pterygoid muscle (LPM) in patients with TMJ dysfunction.MATERIALS AND METHODS: Patients with displacement of the TMJ disk with and without reduction were identified through a review of radiology reports. Absolute measurements of thickness as well as region-of-interest measurements were placed over the 2 heads of the LPM bilaterally on sagittal T1- and T2-weighted images. Statistically significant differences between the superior and inferior heads of the LPM were calculated with use of a 1-tailed Student t test and were correlated with the degree of disk derangement.RESULTS: In patients with disk derangement, significantly increased region-of-interest values on T2- and T1-weighted images were demonstrated within the SHLP. No patients with anatomically normal disks demonstrated a statistically significant difference in region-of-interest values between the superior and inferior heads of the LPMs.CONCLUSION: Correlation between increased region-of-interest values and pathologic alteration of the relationship between the condylar head and disk was identified. In patients with displacement of the anterior disk with and without reduction, region-of-interest values were significantly increased, which indicates abnormal signal intensity involving the superior head of the LPM.